2013
DOI: 10.3389/fnhum.2013.00539
|View full text |Cite
|
Sign up to set email alerts
|

tDCS over the left inferior frontal cortex improves speech production in aphasia

Abstract: In this study, we investigated the combined effect of transcranial direct current stimulation (tDCS) and an intensive Conversational therapy treatment on discourse skills in 12 persons with chronic aphasia. Six short video clips depicting everyday life contexts were prepared. Three videoclips were used to elicit spontaneous conversation during treatment. The remaining three were presented only before and after the therapy. Participants were prompted to talk about the contents of each videoclip while stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 62 publications
3
132
0
10
Order By: Relevance
“…Indeed, the analysis of their lexical skills showed that they produced significantly more phonological errors and more semantic paraphasias than the controls. This is not a new finding, as failure to spontaneously produce fluent and informative speech is the most persistent disabling consequence in persons with aphasia (e.g., Fergadiotis, Wright, & West, 2013;Marangolo et al, 2013;Taylor-Sarno, 1998). Interestingly, a qualitative inspection of the phonological errors showed that these were mostly false starts with fewer phonological paraphasias and neologisms.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the analysis of their lexical skills showed that they produced significantly more phonological errors and more semantic paraphasias than the controls. This is not a new finding, as failure to spontaneously produce fluent and informative speech is the most persistent disabling consequence in persons with aphasia (e.g., Fergadiotis, Wright, & West, 2013;Marangolo et al, 2013;Taylor-Sarno, 1998). Interestingly, a qualitative inspection of the phonological errors showed that these were mostly false starts with fewer phonological paraphasias and neologisms.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, cathodal tDCS decreases cortical excitability, shifting the resting membrane potential toward hyperpolarization and reducing the firing rate of neurons [7][8][9]. A small but growing body of evidence has already indicated that tDCS may provide a supplementary treatment approach for different language deficits in patients with chronic stroke-induced aphasia, such as word-finding difficulties [10][11][12][13], non-fluent speech [12,14] and articulatory disorders [15][16][17][18][19]. In fact, in a preliminary study on a small sample of chronic patients, Marangolo et al [15] showed that repetitive anodal tDCS over the left inferior frontal gyrus (IFG), coupled with language training helped patients to recover from their articulatory disturbances.…”
mentioning
confidence: 85%
“…Thus, the design and interpretation of most of the research addressed only the current delivered over the targeted region. This led to two neuromodulation strategies: either increasing excitability through anodal stimulation over the left hemisphere [5][6][7][8][9]11,[13][14][15][16]20,21] or by decreasing excitability in the contralesional language homologue areas using cathodal stimulation in order to attenuate the inhibition from the intact right hemisphere [10,12,15,[17][18][19][20]. Indeed, while in the context of acute or subacute lesions of the left hemisphere language network there appears to be greater tendency for reallocation of language function into the right-hemisphere perisylvian circuits, many studies have shown that, over time, there is, for a number of patients at least, diminished recruitment of right hemisphere structures for language tasks with a redistribution of language processing back to the left hemispheric perisylvian areas [22][23][24].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…While the first published study [4] that documented tDCS use for aphasia rehabilitation did not include a behavioral treatment protocol, studies since then have combined tDCS with speech-language therapy [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. These initial studies generally included behavioral treatment for anomia and implemented noun retrieval as the outcome measure; more recent studies have included additional behavioral treatments for the recovery of verbs [5,7,13], articulation [9] and discourse productivity [6,8]. However, although the behavioral treatment component has progressed from its initial focus on word retrieval, the electrode montages implemented for the administration of tDCS have remained consistent over time.…”
Section: Introductionmentioning
confidence: 99%